A champagne inspired dual chain-responsive thrombolytic drug release platform based on black phosphorus nanosheets for accelerated thrombolysis. Issue 6 (17th July 2019) - Ding, Xingwei; Hong, Can; Zhang, Guoliang; Liu, Jiaqi; Ouyang, Huan; Wang, Manyu; Dong, Lina; Zhang, Wei; Xin, Hongbo; Wang, Xiaolei
Abstract : A novel dual chain-responsive thrombolytic drug delivery nanoplatform based on black phosphorus nanosheets was designed for thrombolysis. Abstract : To face the clinical challenges related to thrombolytic drugs, such as short blood circulation time, the large dosage required and the side effects of bleeding, the fabrication of a smart controlled thrombolytic drug release nano-system for physical assistant thrombolysis would be very significant. Inspired by champagne, an integrated chain-responsive thrombolytic drug delivery system, uPA@black phosphorus nanosheets-perfluoro- n -pentane@mesoporous silica nanoparticles (uPA@BPNs–PFP@MSNs) was fabricated as a multifunctional platform. The dual chain-responsive thrombolytic drug delivery platform, is first triggered by the photothermic effect of the black phosphorus nanosheets using near-infrared (NIR) laser irradiation (808 nm, 0.2 W cm −2 ), followed by accelerated thrombolytic drug release and the generation of bubbles from the phase change of the material. This platform was integrated via electrostatic adsorption and the thrombolysis, stability and cytocompatibility in vitro were assessed. Additionally, a murine acute jugular vein thrombosis model was built to evaluate the thrombolysis, biosafety and distribution in vivo . In light of these results, the platform has potential applications for delivering thrombolytic drugs safely and accelerating thrombolysis with a reduced dose of drugs clinically.